Cybelle McFadden. Gendered Frames, Embodied Cameras: Varda, Akerman, Cabrera, Calle, and Maïwenn. Lanham: Farleigh Dickinson UP, 2014. xii + 233 pp. - Lauren Van Arsdall (Studies in 20th & 21st Century Literature, 2016)
Review of Cybelle McFadden. Gendered Frames, Embodied Cameras: Varda, Akerman, Cabrera, Calle, and Maïwenn. Lanham: Farleigh Dickinson UP, 2014. xii + 233 pp.
Keywords: Agnès Varda; Chantal Akerman; Sophie Calle; Maïwenn; Dominique Cabrera; French cinema; Female filmmakers